When is CO most dangerous: Safety issues at festivals - Nyombi, Antony; Wessling, Roland; Williams, Mike (Cranfield University, 2018)
This video describes the preliminary work done to show the production of CO at various temperatures as charcoal burns.
Keywords: 'Caron monoxide'; 'charcoal combustion tests'; 'Analytical Chemistry not elsewhere classified'